Antibacterial and Anti-Urease Activities of Chloropheniramine maleat, Paracetamol and Clarithromycine - Sinem Aydın (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2019)
This paper presents anti-urease and antibacterial activities of chloropheniramine maleat, paracetamol andclarithromycine. Antibacterial activity of the compounds was investigated against Salmonella enterica,Enterobacter aerogenes, Bacillus subtilis, Proteus vulgaris, Gordonia rubripertincta, Klebsiella pneumoniae andEnterococcus faecalis. Moreover, anti-urease activity of the compounds was searched. All tested compoundsdemonstrated antibacterial action with varying degree except for chloropheniramine maleat. Chloropheniraminemaleat, paracetamol and chlarithromycine exhibited higher activity than thiourea. The data obtained from thestudy, chloropheniramine maleate, paracetamol and clarithromycin are thought to be useful as new ureaseinhibitors and the present study should be supported by further studies. Furthermore, it is thought that paracetamolhas antibacterial properties and therefore can be used as an alternative to antibiotics